2017
DOI: 10.1117/1.nph.4.4.041501
|View full text |Cite
|
Sign up to set email alerts
|

Whole mouse brain imaging using optical coherence tomography: reconstruction, normalization, segmentation, and comparison with diffusion MRI

Abstract: An automated massive histology setup combined with an optical coherence tomography (OCT) microscope was used to image a total of [Formula: see text] whole mouse brains. Each acquisition generated a dataset of thousands of OCT volumetric tiles at a sampling resolution of [Formula: see text]. This paper describes techniques for reconstruction and segmentation of the sliced brains. In addition to the measured OCT optical reflectivity, a single scattering photon model was used to compute the attenuation coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 58 publications
(76 reference statements)
1
49
0
Order By: Relevance
“…For comparison purposes, more details about the different imaging techniques are provided in Table 1. Figure 1A,C come from our previous work [16]. For more information about the images presented, consult the appropriate references.…”
Section: Intrinsic Optical Contrast Imaging (Ici) Of Brain Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…For comparison purposes, more details about the different imaging techniques are provided in Table 1. Figure 1A,C come from our previous work [16]. For more information about the images presented, consult the appropriate references.…”
Section: Intrinsic Optical Contrast Imaging (Ici) Of Brain Tissuementioning
confidence: 99%
“…OCT/PS-OCT/SDOCT 90 dB-110 dB [21] 6 × 6 × 3.5 µm 3 [19] 25 × 25 × 25 µm 3 [16] Fast (4 cm 3 /h) [19] NIR-IR Autofluorescence TPEFm Highly variable [22] 1 × 1 × 2.5 µm 3 [12] Slow (190 mm 3 /h) [12] NIR PAM~65 dB [23] 1.5 mm × 1.5 mm [24] Fast (18 cm 3 /h) [24] Visible-NIR SHG/ THG >20 dB [25] 0.6 × 0.6 × 2 µm 3 [26] Slow (125 µm 3 /h) [26] NIR-IR SRS/CARS >20 dB [27] 0.3 × 0.3 × 1.5 µm 3 [28] Slow (4000 µm 3 /h) [28] NIR-IR…”
Section: Imaging Technique Sensitivity Spatial Resolution (Voxel Sizementioning
confidence: 99%
“…The raw data were labeled on a 3-D grid to perform a tile registration optimization using a phasecorrelation pairwise registration method inspired by Preibisch et al 35 and developed by Lefebvre et al 31 Stitching of the XY planes was done using a Laplacian diffusion method with a blending width of 0.2 in units of overlap size fraction. 31 After reconstruction, a maximum intensity profile (MIP) was applied on 250-μm-thick slabs. In some instances, we discarded unclear slices caused by issues described later in this report.…”
Section: Image Reconstructionmentioning
confidence: 99%
“…Ragan et al 30 demonstrated that coupling a two-photon microscope with a vibratome and a mechanical stage enabled full 3-D fluorescent imaging of the mouse brain. Optical coherence tomography (OCT) was also demonstrated to yield contrasted images of WM [31][32][33][34] that could be correlated to diffusion MRI.…”
Section: Introductionmentioning
confidence: 99%
“…It is meaningful for future research in brain imaging. Whole brain imaging has been developed through techniques for reconstruction and segmentation of sliced brains (43), and quantitative analysis make brain imaging a more practical clinical value (44). However, whole brain imaging is unnecessary with OCT-based system in intraoperative brain imaging, while a large-field view can provide a great amount of information for a specialist to guide and identify brain tissue feature.…”
Section: Brain Nerve Fiber Bundle Imaging Based On Functional Oct/ocmmentioning
confidence: 99%